2023
DOI: 10.1186/s12916-023-02937-0
|View full text |Cite
|
Sign up to set email alerts
|

Development of consensus-driven SPIRIT and CONSORT extensions for early phase dose-finding trials: the DEFINE study

Abstract: Background Early phase dose-finding (EPDF) trials are crucial for the development of a new intervention and influence whether it should be investigated in further trials. Guidance exists for clinical trial protocols and completed trial reports in the SPIRIT and CONSORT guidelines, respectively. However, both guidelines and their extensions do not adequately address the characteristics of EPDF trials. Building on the SPIRIT and CONSORT checklists, the DEFINE study aims to develop international c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(20 citation statements)
references
References 110 publications
0
20
0
Order By: Relevance
“…A methodological review of published EPDF trials identified features and deficiencies in reporting to inform the initial generation of the candidate items for CONSORT-DEFINE,2940 based broadly on existing reporting guidelines or recommendations including CONSORT 2010,3738 SPIRIT 2013,46 Adaptive designs CONSORT Extension,18 a checklist proposal for phase 1 dose-finding cancer trials,47 as well as consultation with experts. Further candidate items were generated through the analysis of peer reviewed literature, unpublished or grey literature (eg, regulatory and industry advisory documents), citation tracking, and expert opinion 48…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A methodological review of published EPDF trials identified features and deficiencies in reporting to inform the initial generation of the candidate items for CONSORT-DEFINE,2940 based broadly on existing reporting guidelines or recommendations including CONSORT 2010,3738 SPIRIT 2013,46 Adaptive designs CONSORT Extension,18 a checklist proposal for phase 1 dose-finding cancer trials,47 as well as consultation with experts. Further candidate items were generated through the analysis of peer reviewed literature, unpublished or grey literature (eg, regulatory and industry advisory documents), citation tracking, and expert opinion 48…”
Section: Methodsmentioning
confidence: 99%
“…Two hundred and six participants from 24 countries voted in round one (March-May 2022), and 151 participants voted in round two (May-June 2022) of the Delphi survey. Round two participants were shown the distribution of the item rating as well as their previous rating if they had completed round one 48…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A contributing factor to poor reporting quality could be that CONSORT 2010 was not designed for early phase dose‐finding trials with some important elements being either difficult to comply with or missing from the existing guidance. It was recognized that a modified guideline was required to improve reporting of phase I/II trials, especially dose (de)‐escalation trials 13,14 . This has now been addressed with the development and publication of the CONSORT – DosE FIndiNg Extension (CONSORT‐DEFINE) reporting guideline 15 .…”
Section: Figurementioning
confidence: 99%
“…While we anticipated various modifications and additions to the standard Spirit and Consort checklists, what took us by surprise was the sheer number of items that emerged as critically important. Furthermore, while we initially expected participation from around 100 people in the Delphi survey, we were astounded to have 206 participants from 24 different countries contribute to shaping the guidelines2.…”
mentioning
confidence: 99%